2020
DOI: 10.1186/s12936-020-03230-8
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of uptake of optimal doses of sulfadoxine-pyrimethamine for prevention of malaria during pregnancy in East-Central Uganda

Abstract: Background: In 2012, the World Health Organization recommended that pregnant women in malaria-endemic countries complete at least three (optimal) doses of intermittent preventive treatment (IPTp) using sulfadoxinepyrimethamine (SP) to prevent malaria and related adverse events during pregnancy. Uganda adopted this recommendation, but uptake remains low in East-Central and information to explain this low uptake remains scanty. This analysis determined correlates of uptake of optimal doses of IPTp-SP in East-Cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 35 publications
7
6
0
Order By: Relevance
“…That study [41] was consistent with ours in not nding an association between SP and urban/rural residence, but it differed in that it did not nd an association between maternal education or wealth and SP doses. Similar to our ndings, wealth was associated with ≥3 doses of SP in Uganda [54] and Nigeria [55].…”
Section: Discussionsupporting
confidence: 90%
“…That study [41] was consistent with ours in not nding an association between SP and urban/rural residence, but it differed in that it did not nd an association between maternal education or wealth and SP doses. Similar to our ndings, wealth was associated with ≥3 doses of SP in Uganda [54] and Nigeria [55].…”
Section: Discussionsupporting
confidence: 90%
“…Those ndings could result from the fact that strategies are more focused on the distribution of preventive measures than the importance of their use [27]. We found the ANC usage as a strong predictor of complete MPM as con rmed in other settings [10,11]. Nevertheless, we can notice through the CART result that ANC is not the solely circumstance to have complete MPM.…”
Section: Discussionmentioning
confidence: 45%
“…However, challenges remain to ensure their optimal use, particularly in countries with high malaria endemicity [9,10]. For instance, in neighbouring country Senegal, a secondary analysis of the Demographic and Health Survey (DHS) 2013-2014 showed that 37.51% of pregnant women used this combination [11].…”
Section: Introductionmentioning
confidence: 99%
“…Wild-type alleles; the lower map shows the ratio of SAK and AAK alleles among wild-type pfdhps alleles (Pearce et al, 2009). reported SP failure across East Africa, with Rwanda and Burundi exceeding the critical 25% value SP failure rates (Rapuoda et al, 2003); this could be due to a low uptake of SP by pregnant women due to weak health system and sub-optimal implementation policy, among other factors (Martin et al, 2020). The pfdhps A581G and pfdhfr I164L mutations, which confer SP resistance, have been found to be unevenly distributed across East Africa, suggesting a high level of SP resistance, as indicated by the prevalence of the K540E mutation, found across East Africa (Naidoo and Roper, 2011).…”
Section: The Spread Of Sulfadoxine-pyrimethamine Resistance In Sub-saharan Africamentioning
confidence: 99%